Assessing Coronal Deformities of the Distal Humerus Using Lateral Radiographs - Krishna, Sathya Vamsi; Kanumuri, Sanjana (Indian Journal of Radiology and Imaging, 2025)
Cubitus deformities are often identified via anteroposterior views of the elbow; however, irradiating both limbs is required in this method to confirm and quantify the deformity. This brief report proposes a new method of evaluating lateral radiographs for the presence of cubitus varus and valgus by identifying a key landmark: the overlap of the trochlea and capitellum within the olecranon and coronoid processes, without a contralateral radiograph. On a lateral radiograph, the relationship of the radio capitular line proximal to the ulnotrochlear line depicts a cubitus valgus deformity and the reverse is true for a cubitus varus deformity. This sign is a reliable method to screen and assess these deformities in a cost-effective and efficient manner.Level of Evidence: Level V.
Keywords: cubitus varus; cubitus valgus; lateral radiographs of the elbow